U.S. Grant : American hero, American myth - Waugh, Joan (Chapel Hill : University of North Carolina Press, 2009)
Ulysses S. Grant was the most famous person in America, considered by most citizens to be equal in stature to George Washington and Abraham Lincoln. Yet today his monuments are rarely visited, his military reputation is overshadowed by that of Robert E. Lee, and his presidency is permanently mired at the bottom of historical rankings. Waugh shows that Grant's reputation and place in public memory closely parallel the rise and fall of the northern version of the Civil War story. During this social transformation, Grant's public image changed as well. By the 1920s, his reputation had plummeted. Most Americans today are unaware of how revered Grant was in his lifetime.
The magnanimous general -- A great soldier might be a baby politician -- The most famous living American -- Historian of the union cause -- Pageantry of woe: the funeral of U.S. Grant -- The nation's greatest hero should rest in the nation's greatest city -- Who's [really] buried in Grant's tomb?
Includes bibliographical references and index
Keywords: Grant, Ulysses S. -- 1822-1885 -- Public opinion -- Influence; United States -- Army; Presidents -- United States; Generals -- United States; Collective memory -- United States; Public opinion -- United States; United States -- History -- Civil War, 1861-1865 -- Public opinion